The Culture of Memory and the Genesis of the Political In Delphic Theology - Kazlauskas, Raimondas (Sociologija. Mintis ir veiksmas, 2018)
[full article and abstract in Lithuanian; abstract in English] This article discusses the genesis of the political by treating this phenomena as a distinctive interaction between political and religious factors. The chirographic culture of memory, which is more characteristic of the Eastern nations, is being compared with the alternative culture of Ancient Greece, the so-called oroacoustic culture of memory. This article also examines the peculiarities of the political consciousness and religious mentality of Ancient Greece. The assumptions of legitimacy are considered as well, which are related to an identity crisis and a war between generations reflected, in theology, by the traditional world of the Fathers (Olympic) and the marginal world of the Sons (Delphic).